The Relations Between the Concentration of Nitrate and Phosphate to Abundance of Dinoflagellates in Enhalus acoroides Beds in Sungai Enam Coastal Waters of Bintan Regency of Riau Islands Province - Dwi Putri Pratiwi; Irvina Nurrachmi; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in June 2015 in Sungai Enam coast of Bintan Island, with the aims to know the difference abundance of dinoflagellates in every station and to knows the relations between nitrate concentration and phosphate concentration to the abundance of dinoflagellates in seagrass beds. The samples were taken from 3 stations with 3 sampling points. The result showed that the average of nitrate concentration was 0.0029 mg/l and the average of phosphate concentration was 0.1219 mg/l. This research identified 10 species of dinoflagellates, with the highest abundance was found in station 1 (0.13 cells/cm2) and the lowest was found in station 2 (0.10 cells/cm2). The results of the simple linear regression of nitrate and phosphate concentration showed a positive relation with dinoflagellates abundance, that means if the concentration of nitrate and phosphate raising the dinoflagellates abundance was also increasing.Key words: nitrate, phosphate, Dinoflagellates, Sungai Enam Waters, Bintan